2012
DOI: 10.3390/catal2010068
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Liquid-Phase Catalytic Conversion of Ethanol to 1-Butanol over Aluminium Oxide—The Effect of the Active Metal on the Selectivity

Abstract: Direct catalytic valorization of bioethanol to 1-butanol over different alumina supported catalysts was studied. Thirteen (13) heterogeneous catalysts were screened in search for the optimal material composition for direct one-pot conversion of ethanol to 1-butanol. For the most promising catalyst, a 25% ethanol conversion with 80% selectivity (among liquid carbon products) to 1-butanol could be reached at 250 °C. Additionally, the reaction kinetics and mechanisms were further investigated upon use of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 17 publications
1
92
0
Order By: Relevance
“…An almost complete conversion of BuOH can be obtained for temperatures below 350°C, while at higher temperatures, a minor fraction of BuOH (<5 mol%) remains unreacted. Riittonen et al 68 reported a theoretical maximum conversion of 98.5% for the condensation of ethanol to n-butanol at 250°C and 70 bar, and Olcese and Bettahar 101 calculated a thermodynamically favorable equilibrium for the Guerbet reaction of ethanol both in vapor and in liquid phase. The first step in the generally accepted reaction pathway is the dehydrogenation of the reagent alcohol to the corresponding aldehyde or ketone (Scheme 2, R2).…”
Section: Reaction Mechanisms and Thermodynamic Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…An almost complete conversion of BuOH can be obtained for temperatures below 350°C, while at higher temperatures, a minor fraction of BuOH (<5 mol%) remains unreacted. Riittonen et al 68 reported a theoretical maximum conversion of 98.5% for the condensation of ethanol to n-butanol at 250°C and 70 bar, and Olcese and Bettahar 101 calculated a thermodynamically favorable equilibrium for the Guerbet reaction of ethanol both in vapor and in liquid phase. The first step in the generally accepted reaction pathway is the dehydrogenation of the reagent alcohol to the corresponding aldehyde or ketone (Scheme 2, R2).…”
Section: Reaction Mechanisms and Thermodynamic Considerationsmentioning
confidence: 99%
“…7,[106][107][108][109] For liquid phase reactions, hence at increased pressure, the detrimental effect of water on conversion and selectivity is often reported. 36,68,[110][111][112] Although this is generally caused by a deactivating effect on the catalyst, water could also influence the thermodynamic equilibrium of the aldol condensation. It might slow down the desired reaction pathway, thereby leaving intermediate aldehydes …”
Section: Reaction Mechanisms and Thermodynamic Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors observed that the hydrogenation capacity of the catalyst as well as selectivity to n-butanol increases with increase in concentration of Mg ( Carvalho et al 2012). Riittonen et al (2012) studied one-pot liquid-phase catalytic conversion of ethanol to 1-butanol over aluminium oxide. They examined and screened thirteen (13) heterogeneous catalysts in search for the optimal material composition for direct one-pot conversion of ethanol to 1-butanol.…”
Section: Catalysts For the Production Of Butanolmentioning
confidence: 99%